Strategiczna rachunkowość zarządcza : ujęcie modelowe - Nita, Bartłomiej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper describes the genesis and definition of the strategic management accounting concept. The need for integrating the accounting approach and the strategic perspective in corporate management was justified and the role of accounting in the process of strategic management was indicated. In the article the main tasks and instruments of strategic management accounting were proposed and attributed to the particular stages of strategic management: strategy analysis, planning, implementation and strategy control. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 274-289